Counselors experiences in handling the counseling session on the gay and lesbian clients: factors causing the occurence of gay and lesbian behavior - Mohd Faradi, Mohamed Ghazali; Siti Hajar, Jamal; Nasrudin, Subhi; Salleh, Amat (2019)
Gay and lesbian phenomenon has become talk of the town in Malaysia nowadays. It is considered as a controversial issue as it has started to expand since ancient times. There are various notions and perceptions of society towards gay and lesbian culture. Therefore, the primary objective of this study is to identify the driving factors of the clients’ involvement in gay and lesbian world based on counselors’ experiences in handling their counseling sessions. The study has used qualitative study design involving semi structured in-depth interviews on counselors’ experiences while handling the gay and lesbian cases. Purposive sampling is employed in interviewing the counselors who have been identified by the researcher to have information in counseling session management with regard to the causing factors of the client’s involvement in gay and lesbian activities. Data were analyzed by studying the transcription of interview recording and identifying the themes that emerged based on the objectives of the study with the help of the N'vivo 11 program. Based on the analyzed data, there are four themes that emerged from the interview results; (i) family factor, (ii) education and (iii) sexual abuse and (iv) environment. The results demonstrate that counselors should possess knowledge and information regarding the clients so that they can help and assist these individuals in obtaining better lives. These gay and lesbian individuals should be provided with moral and spiritual support since some of them are the victims of circumstances. Therefore, the implication of the study is so that it can enhance a counselor’s knowledge if he or she wants to provide better counseling services to their clients (the gay and lesbian individuals). Apart from that, the findings are accentuated to be able to assist educators in counseling field so that the trained counselors will be more competent in dealing with gay and lesbian issue.